Effect of Footwear Type on Biomechanical Risk Factors for Knee Osteoarthritis - Malus, Jan; Urbaczka, Jan; Rygelova, Marketa; Casula, Victor; Nieminen, Miika; Monte, Andrea; Horka, Veronika; Uchytil, Jaroslav (Orthopaedic journal of sports medicine, 2023)
BACKGROUND: Regular walking in different types of footwear may increase the mediolateral shear force, knee adduction moment, or vertical ground-reaction forces that could increase the risk of early development of knee osteoarthritis (OA). PURPOSE: To compare kinematic and kinetic parameters that could affect the development of knee OA in 3 footwear conditions. STUDY DESIGN: Controlled laboratory study. METHODS: A total of 40 asymptomatic participants performed walking trials in the laboratory at self-selected walking speeds under barefoot (BF), minimalistic (MF), and neutral (NF) footwear conditions. Knee joint parameters were described using discrete point values, and continuous curves were evaluated using statistical parametric mapping. A 3 × 1 repeated-measures analysis of variance was used to determine the main effect of footwear for both discrete and continuous data. To compare differences between footwear conditions, a post hoc paired t test was used. RESULTS: Discrete point analyses showed a significantly greater knee power in NF compared with MF and BF in the weight absorption phase (P < .001 for both). Statistical parametric mapping analysis indicated a significantly greater knee angle in the sagittal plane at the end of the propulsive phase in BF compared with NF and MF (P = .043). Knee joint moment was significantly greater in the propulsive phase for the sagittal (P = .038) and frontal planes (P = .035) in BF compared with NF and MF and in the absorption phase in the sagittal plane (P = .034) in BF compared with MF and NF. A significant main effect of footwear was found for anteroposterior (propulsion, ↑MF, NF, ↓BF [P = .008]; absorption, ↑BF, MF, ↓NF [P = .001]), mediolateral (propulsion, ↑MF, NF, ↓BF [P = .005]; absorption, ↑NF, MF, ↓BF [P = .044]), and vertical (propulsion, ↑NF, BF, ↓MF [P = .001]; absorption, ↑MF, BF, ↓NF [P < .001]) ground-reaction forces. Knee power showed a significant main effect of footwear (absorption, ↑NF, MF, ↓BF [P = .015]; propulsion, ↑MF, NF, ↓BF [P = .039]). CONCLUSION: Walking in MF without sufficient accommodation affected kinetic and kinematic parameters and could increase the risk of early development of knee OA.
Keywords: SPM; walking; minimalistic; barefoot; knee; osteoarthritis; footwear